Neuro-urological surveillance of Spina bifida in Morocco - Herman Azanmasso; Essohouna Tchonda; Etienne Alagnide; Samira Lahrabli; Fatima Lmidmani; Abdellatif El Fatimi (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2019)
Objective: Spina bifida is one of the first caused of disability with children in USA. This incidence was estimated to 3.5 per 10000 habitants. In France, it was mostly, 0.5 per 1000 habitants. The improvement in neuro surgy and in urology allowed a veritable reduction of mortality with spina bifida.  Method: It was a retrospective descriptive and analytic study with children suffering of spina bifida and followed up between january 2013 and december 2015 at the department of Physical Medicine of Casablanca. Results: Twenty six patients were followed up. The average age was 11.9 +/- 5.8 years. These urinary disorders were frequency 100%, urinary incontinence 65.4%, urgency 73.1% and intermittent stream or training 46.2% with significant post void residual 26.9%. In urodynamic studies, bladder sphincter dysynergia was 7.7%, low bladder compliance with 61.5%, phasic or terminal detrusor overactivity 84.6% with 38.5% dangerous. In ultrason, they were 23.1% fight bladder with urinary retrogress and two children had dilatation of upper urinary tract and end stage renal disease, in list for renal transplantation.  Conclusion: The children with spina bifida need follow-up and managment of requirement of care relative to the weight of this affection for children and their parents.